Population and demographic structure of blue sheep (Pseudois nayaur) and Himalayan tahr (Hemitragus jemlahicus) in Dhorpatan Hunting Reserve, Nepal - Thakuri, Bishnu Singh; Chetri, Madhu; Thapa, Shyam Kumar; Tumbahanphe, Ajit; Dhakal, Bed Kumar; Subedi, Naresh (Nepalese Journal of Zoology, 2024)
The blue sheep and Himalayan thar were counted using the vantage count method to obtain population and demographic status in Dhorpatan Hunting Reserve, western Nepal between April and May of 2021. We used binoculars (Olympus 10 × 50 and Nikon 10 × 42) and spotting scopes (Nikon 20–60 × 75 and Bushnell 20–60 × 65) for identifying the animals into class and sex categories. A total of 1290 blue sheep were counted in six hunting blocks of DHR with an apparent density of 2.2 animals/km2 in 79 herds (mean heard size: 16.33 ± 1.53). Maximum numbers of blue sheep were recorded from Dogadi (n=361) and low numbers in Sundaha block (n=89). We found a significant difference in the average herd size of blue sheep among the six blocks, possibly due to human-induced disturbances as some blocks are relatively accessible and closer to human settlements. However, there was no significant difference in the average male and female sex ratio and density between hunting blocks. Similarly, a total of 744 Himalayan tahr were observed in six hunting blocks with an apparent density of 1.49 animal/km2 in 50 herds (mean heard size: 14.88±2.29). Maximum numbers of tahr were recorded from Ghustung (n=387) and low numbers in Surtibang block (n=12). We found a significant difference in the average herd size of Himalayan tahr and male to female sex ratio, but not a significant difference in density between hunting blocks. Regular study of population dynamics in the context of trophy hunting is very crucial. Thus, annual surveys of these game species are recommended for designing sustainable game trophy hunting in the region.